Antibiotic Resistance of Uropathogenic Escherichia coli Isolated from Patients with Urinary Tract Infections at the Urological Inpatient Facility of the Saratov Clinical Hospital - A. V. Kazantsev; M. V. Proskuryakova; E. S. Kazakova; N. A. Osina; I. G. Shvidenko; A. N. Mikerov (Проблемы особо опасных инфекций)
The aim of the work was to study the profile of antibiotic resistance of uropathogenic Escherichia coli strains isolated from patients with urinary tract infections in the urological inpatient facility of the clinical hospital in the Saratov city, depending on appurtenance to phylogenetic groups and subgroups, as well as O-serogroups.Materials and methods. We assessed sensitivity/resistance to 25 different antibacterial drugs in 102 strains of uropathogenic E. coli. The studies were carried out using the disk diffusion method. The production of extended spectrum beta-lactamases was evaluated by the double disk method. Carbapenemase output was determined using the CIM test. The PCR method was applied to determine appurtenance to phylogenetic groups and subgroups, O-serogroups, as well as the frequency of occurrence of the mcr‑1, mcr‑2, mcr‑3, mcr‑4, mcr‑5 genes encoding the proteins that mediate the development of resistance to colistin.Results and discussion. It has been established that all strains of uropathogenic E. coli are more or less resistant to antibacterial drugs. All studied 102 strains showed resistance to 23 antibacterial drugs from 8 functional groups. The resistance of uropathogenic E. coli had certain differences depending on belonging to phylogenetic groups and subgroups, O-serogroups. Strains of uropathogenic E. coli with high resistance (up to 100 %) belonged to the B23 phylogenetic group, the main representatives of which are cultures of the most common O-25 serogroup. The production of extended-spectrum beta-lactamases has been phenotypically confirmed for 69 (67.6 %) strains. No carbapenemaseproducing cultures were found in the study. The mcr‑1 and mcr‑2 genes encoding resistance to colistin have been identified in 3 uropathogenic E. coli strains (2.9 %).